Antigenic and Functional Expression of Tissue Factor in Endotoxin Stimulated U937 Cells: Regulation of Activity by Calcium Ionophore A23187 - Consonni, R; Bertina, R M (Thrombosis and Haemostasis, 1995)
Tissue Factor (TF) is a transmembrane glycoprotein that serves as cofactor for Factor VII (FVII) in the initiation of blood coagulation and that is differentially expressed in a number of cell types, being constitutively expressed in some and inducible in others. We studied the localization and the functional activity of TF in monocytic leukemia U937 cells at different time intervals after lipopolysaccharides (LPS) stimulation, and the effect of calcium ionophore on the surface expressed TF.Exposure of U937 cells to 10 µg/ml LPS resulted in a time dependent increase of TF expression that reached a maximum at 12 h for TF antigen and at 24 h for TF activity. Blocking of surface TF with inhibitory anti-TF antibody abolished >93% of the activity of lysed cells stimulated for 24 h, while it blocked only 80% of the activity in lysed cells stimulated for 12 h suggesting that at that time about 20% of TF is not accessible for the antibody. Even at 24 h when the specific activity of surface expressed TF is 5.5 times higher than at 12 h, this specific activity is still 10 fold lower than that of TF in lysed cells. Addition of Ca++ ionophore A23187 to LPS stimulated cells resulted in a fast increase of TF activity that was dependent on the dose of ionophore, on the extracellular Ca++ concentration and on the time that the cells had been incubated with LPS. Kinetic analysis of Factor X hydrolysis by the TF/FVII complex demonstrated that the addition of ionophore resulted in an increase of both the Vmax and the apparent Km, however, without affecting the catalytic efficiency of the reaction.These data suggest that in U937 cells part of the TF induced by LPS is cryptic, that the specific activity of surface expressed tissue factor increases with time and that intracellular changes in Ca++ concentration can be important in the regulation of the expression of TF activity on the cell surface.